RNA-Seq Data Mining: Downregulation of NeuroD6 Serves as a Possible Biomarker for Alzheimer’s Disease Brains - Satoh, Jun-ichi; Yamamoto, Yoji; Asahina, Naohiro; Kitano, Shouta; Kino, Yoshihiro (Disease Markers, 2014)
Alzheimer’s disease (AD) is the most common cause of dementia worldwide with no curative therapies currently available. Previously, global transcriptome analysis of AD brains by microarray failed to identify the set of consistently deregulated genes for biomarker development of AD. Therefore, the molecular pathogenesis of AD remains largely unknown. Whole RNA sequencing (RNA-Seq) is an innovative technology for the comprehensive transcriptome profiling on a genome-wide scale that overcomes several drawbacks of the microarray-based approach. To identify biomarker genes for AD, we analyzed a RNA-Seq dataset composed of the comprehensive transcriptome of autopsized AD brains derived from two independent cohorts. We identified the core set of 522 genes deregulated in AD brains shared between both, compared with normal control subjects. They included downregulation of neuronal differentiation 6 (NeuroD6), a basic helix-loop-helix (bHLH) transcription factor involved in neuronal development, differentiation, and survival in AD brains of both cohorts. We verified the results of RNA-Seq by analyzing three microarray datasets of AD brains different in brain regions, ethnicities, and microarray platforms. Thus, both RNA-Seq and microarray data analysis indicated consistent downregulation of NeuroD6 in AD brains. These results suggested that downregulation of NeuroD6 serves as a possible biomarker for AD brains.